Development of CRISPR Cas9, spin-off technologies and their application in model construction and potential therapeutic methods of Parkinson’s disease - Qu, Jiangbo; Liu, Na; Gao, Lu; Hu, Jia; Sun, Miao; Yu, Dongyi (Frontiers in Neuroscience, 2023)
Parkinson's disease (PD) is one of the most common degenerative diseases. It is most typically characterized by neuronal death following the accumulation of Lewis inclusions in dopaminergic neurons in the substantia nigra region, with clinical symptoms such as motor retardation, autonomic dysfunction, and dystonia spasms. The onset and process of PD is influenced by both environmental and genetic factors. The exact molecular mechanism of its pathogenesis has not been revealed up to now. And there is a lack of effective treatments for PD, which places a burden on patients, families, and society. CRISPR Cas9 is a powerful technology to modify target genomic sequence with rapid development. More and more scientists utilized this technique to perform research associated neurodegenerative disease including PD. However, the complexity involved makes it urgent to organize and summarize the existing findings to facilitate a clearer understanding. In this review, we described the development of CRISPR Cas9 technology and the latest spin-off gene editing systems. Then we focused on the application of CRISPR Cas9 technology in PD research, summarizing the construction of the novellatest PD-related medical models including cellular models, small animal models, large mammal models. We also discussed new directions and target molecules related to the use of CRISPR Cas9 for PD treatment from the above models. Finally, we proposed the view about the directions for the development and optimization of the CRISPR Cas9 technology system, was proposed and an outlook on its future application to PD and gene therapy in the futurewas conducted.. All these results provided a valuable reference and enhance understanding for studying PD.